Psychometric evaluation of the child attitude toward illness scale—sibling version. Issue 4 (7th August 2020) - Bellin, Melissa H.; Margolis, Rachel H.F.; Austin, Joan; Sacco, Paul; Thompson, Anna; Bookman, Jaclyn R. MacFarlane; Sawin, Kathleen J.
ABSTRACT: The Child Attitude Toward Illness Scale (CATIS) is an established measure of how CSHCN perceive the impact of chronic conditions on their lives. We tested the psychometric properties of the CATIS adapted for use with siblings (CATIS-S) of youths with spina bifida (SB), a complex congenital birth defect. Confirmatory factor analysis (CFA) tested the factor structure of the CATIS-S in a sample of 208 adolescent siblings of youths with SB. Construct validity was ascertained by evaluating relationships between the CATIS-S and measures of psychosocial functioning. CFA yielded a 12-item two-factor solution comprised of an Emotion subscale ( α  = 0.85) and Social subscale ( α  = 0.76). Construct validity was indicated through significant associations between CATIS-Emotional and self-concept ( r = 0.30, p < .001) and parent-perceived SB severity ( r = −0.17, p = .01), as well as CATIS-Social and sibling conflict ( r = −0.26, p < .001), behavior problems ( r = −0.37, p < .001), and self-concept ( r = 0.50, p < .001). Results provide preliminary support for a 12-item, two-factor version of the CATIS-S. Social workers can administer the CATIS-S to assess the psychosocial strengths and needs of youths who have siblings with SB and provide targeted interventions to those at-risk to improve their psychosocial functioning.